ANALISIS DEBIT KEBUTUHAN AIR UNTUK IRIGASI DI BRINGINSILA KABUPATEN SUMBAWA - NOVRIANSYAH MAULANA; MUHAMAD YAMIN; KUSMIANTI KUSMIANTI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
The purpose of this study was to calculate the discharge as well as the availability and demand for water in the Bringinsila irrigation secondary channel. Based on the results of the analysis of rainfall, the discharge (Q) at the Bringinsila dam was obtained from January to December, respectively; 45 m3/s, 38 m3/s, 18 m3/s/, 31 m3/s, 45 m3/s, 42 m3/s, 44 m3/s, 46 m3/s, 48 m3/s, 49 m3/s , 43 m3/s, 35 m3/s.After analyzing monthly rainfall from the Utan rain station, Utan Subdistrict, Sumbawa Regency, it can be concluded that the water needs for farmers in the Bringinsila irrigation area are still sufficient, this is based on the results of the analysis starting from processing preparation work in November until the first harvest period, the water discharge is 25.78 m3/s while demand is 9.43 m3/s